Nascita ed evoluzione del distretto orafo di Arezzo, 1947-2001 - Luciana, Lazzeretti (Firenze University Press, 2003)
This book, generated by the creation of a database on the population of enterprises and their characteristics, illustrates the process of development of the Arezzo gold and jewellery system. It is a significant case in view of its international prestige and the use of highly specialised manpower, and at the same time interesting in terms of type, since it represents an emerging district produced by gemmation from a large enterprise. The analysis offers insight into the process of district development and a methodological support for ulterior investigations. At the same time, it also represents a tool for an understanding of the long-term economic dynamics characterising one of the most vital productive areas of Tuscany.